Convívio da família diante da diálise peritoneal no domicílio: implicações para o cuidado de enfermagem - Timm, Arlete Maria Brentano (2013)
The families are inserted in a context of transformations in conceptions, notions and structures, because of the economical, political, social and cultural changes of the society, and they can reflect in the health patterns and diseases of people. The purpose of this study is to comprehend how a family live with the necessity of one of its members to make peritoneal dialysis in domicile. The study was done with a qualitative, explored and described approach. The subjects of the research were seven families that have had one of their members in peritoneal dialysis, all of them living in Santa Maria, Rio Grande do Sul, totalizing fifteen persons. The captivation place of the subjects was the Renal Clinic of Santa Maria. The data collections were made through the construction of a familiar genogram and interviews with families in their homes, from March to May, in 2012. The information was submitted to a thematic analysis. It has followed the ethical principles of Resolution No. 196/96, of the National Health Council of the Ministry of Health for research involving human beings. The results of the analysis are described and discussed in three articles. The investigation of the dynamics of the families has raised questions like: the realization of the techniques of dialysis by the members of the families and their challenges; the presence or absence of cooperation among the families members in face to situation of chronic disease; the sick family member dependence; and the social and emotional alterations of the families in front of this reality. The families repercussions are: the family changes its routine to attend the treatment requirements; the commitment of the leisure time activities of the families; the necessity of the family to be closer to the sick familiar; and the needs of the family members to adapt themselves to the limitations and restrictions of the sick familiar. The strategies found by the families were: to adapt the treatment schedule with the other activities; to acquire knowledge and develop abilities to make peritoneal dialysis at home; to adequate the physical environment in the residence; and to adapt the routine of the family to face the sickness and the treatment of its familiar member. It believes that the results of the research can contribute to improve the quality of the assistance give to patients and their families living with peritoneal dialysis at home. It concludes that many alterations occur in these families such as social, financial, professional, in the leisure activities, but these changes adjust themselves to make possible the treatment and the preservation of the family relationships. So, if the characteristics of each family are known, it is possible to the nurse acts closer to the individual needs in face of the treatment that demands a great familiar involvement, in order to have a dialogue that helps everybody to overcome the difficulties and to comprehend the expectations.